EXOTICISMS IN VOCABULARY - Samad Yuldoshev (Modern American Journals, 2025)
Today, the world is developing and expanding rapidly. And so is language. Every day, various linguistic features are being identified by linguists, and before being presented to the general public, these linguistic units are being studied and analyzed. Undoubtedly, the results and fruits of all research, first of all, serve to benefit humanity, to enable it to communicate freely, to achieve brevity and conciseness in both written and oral speech, and, at the same time, to achieve clarity.